A Singapore perspective : impact of disclosure and board independence on firm performance. - Chua, Zi Qin. (2010)
This study examines the impact of the Singapore’s Code of Corporate Governance on firm’s performance. Specifically, we examine how increased board structure disclosure and compliance with board independence affect operating performance and market valuation. Using a difference-in-differences approach, we find that firms are rewarded with an increase in Tobin’s Q upon greater disclosure of board independence as recommended by the Code. In addition, for those firms that disclose their board structure prior to the Code introduction, we find that many are already complying with the recommended board independence. However, there is much variation in terms of the proportion of independent directors across firms. Interestingly, firms that have more than 50% independent directors on their boards do not have better performance. Consistent with the Code’s recommendation of at least 33% independent directors, we find that firms with board independence in the range of 33% to 50% have the best operating performance.